KEPEMILIKAN TANAH SECARA GUNTAI (ABSENTEE) DI KECAMATAN GUNUNG TOAR BERDASARKAN PERATURAN PEMERINTAH NOMOR 224 TAHUN 1961 JO PERATURANPEMERINTAH NOMOR 41 TAHUN 1964 TENTANG PELAKSANAAN PEMBAGIAN TANAH DAN PEMBERIAN GANTI KERUGIAN - Rahmat Septiadi; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Land has an important role for human life because human life cannot be separated from land.In the regulations that have been set forth in Article 10 paragraph 1 of Law number 5 of 1960concerning Basic Agrarian Regulations it stipulates that: "Every person and legal entity that has aright to agricultural land is in principle obliged to work or actively cultivate it himself by preventextortion. According to the Basic Agrarian Law, it expressly prohibits land aggregation. The aim is tofind out the factors of the occurrence of guntai land (absentee) in Gunung Toar District and to find outthe Prevention Efforts Against Guntai Land Ownership (absentee) in Gunung Toar District.The research method is an important factor for scientific writing. A scientific work must containtruth that can be accounted for scientifically so that the results of the scientific work can approach areal truth. Legal research is carried out in the context of efforts to develop law and respond to newlegal issues that are developing in society. Without legal research, legal development will not beoptimal. The author uses a type of sociological or empirical legal research. Sociological research isresearch on law observing what are the characteristics of a community's behavior in an area in anaspect of social life. The location of the research conducted by the author is in Gunung Toar District,Kuantan Singingi Regency because in Gunung Toar District there is still absentee land ownership.Laws and regulations as guidelines for the implementation of clear and firm regulationsregarding restrictions on land ownership which are increasing on the control of agricultural land. Inarticles 12 and 13 of the UUPA the government in the agrarian field which is monopoly can only becarried out by law. Kuantan Singingi Regency, especially in Gunung Toar Subdistrict, there are stillmany absentee/guntai lands. So far, the Defense Office has indeed not done anything concrete tosupport the effectiveness of the ban on absentee/guntai land ownership. The results of the interview withMr. Riko Syahrudin S.H explained that there were several steps that had been taken by the ATR/BPN ofthe Kuantan Singingi Regency in carrying out prevention and control of agricultural land by people orfamilies who lived outside the area where the land was located or also called absentee/guntai land. Inline with the objectives to be achieved through the Defense Orderly Chess program, especially defenseand orderly use of land, the Agrarian Spatial Office/National Land Agency of Kuantan SingingiRegency has made efforts, namely: law enforcement by holding directed and widely continuous legalcounseling.Keywords: Land, Guntai (Absentee), Ownership.